Determination of Heavy Metal and Nutrient Contents and Potential Use of Tobacco Waste Compost in Vegetable Seedling Production - Gebologlu, Naif; Durukan, Aysegul; Camci Cetin, Sema (Asian Journal of Chemistry, 2016)
The importance of organic waste usage has become crucial both in reducing environmental problems and facilitating this potential in organic farming. The objectives of this study were to compare nutrient and heavy metal contents of tobacco waste compost and investigate their effects on pepper, tomato, eggplant and cucumber seedling production. Compost media were compared with peat and tobacco waste with perlite, pumice, manure, quail manure and soil mixture in terms of nutrient and heavy metal. Results showed that heavy metal contents of medium were under the limit of hazard level. However, these media contained high level of nutrient contents, particularly N, P, K, Ca Mg. EC and pH values in these media varied between 0.58-1.50 mmos.com and 5.86-7.74, respectively. The results showed that tobacco waste compost may be used as an organic fertilizer due to the high nutrient and low heavy metal contents.